Language is not isolated from its wider environment: Vocal tract influences on the evolution of speech and language. (May 2017) - Dediu, Dan; Janssen, Rick; Moisik, Scott R.
Abstract: Language is not a purely cultural phenomenon somehow isolated from its wider environment, and we may only understand its origins and evolution by seriously considering its embedding in this environment as well as its multimodal nature. By environment here we understand other aspects of culture (such as communication technology, attitudes towards language contact, etc.), of the physical environment (ultraviolet light incidence, air humidity, etc.), and of the biological infrastructure for language and speech. We are specifically concerned in this paper with the latter, in the form of the biases, constraints and affordances that the anatomy and physiology of the vocal tract create on speech and language. In a nutshell, our argument is that (a) there is an under-appreciated amount of inter-individual variation in vocal tract (VT) anatomy and physiology, (b) variation that is non-randomly distributed across populations, and that (c) results in systematic differences in phonetics and phonology between languages. Relevant differences in VT anatomy include the overall shape of the hard palate, the shape of the alveolar ridge, the relationship between the lower and upper jaw, to mention just a few, and our data offer a new way to systematically explore such differences and their potential impact on speech. These differences generate very small biases that nevertheless can be amplified by the repeated use and transmission of language, affecting language diachrony and resulting in cross-linguistic synchronic differences. Moreover, the same type of biases and processes might have played an essential role in the emergence and evolution of language, and might allow us a glimpse into the speech and language of extinct humans by, for example, reconstructing the anatomy of parts of their vocal tract from the fossil record and extrapolating the biases we find in present-day humans. Highlights: Language is a multimodal system that is influenced by its wider environment. There is inter-individual and inter-population variation in the vocal tract. Vocal tract anatomy influences speech production. These biases might result in phonetic and phonological diversity. Language evolution needs a broader perspective on language and speech.